Teacher Observation Skills Scale: Validity and Reliability - Abdullah Cetin (International Journal of Contemporary Educational Research, 2024)
The present research aims to develop a valid and reliable instrument to measure teacher observation skills. The research was conducted during the 2023-2024 academic year with a total of 648 teachers. Data were collected through online survey methods. Expert opinion was consulted for the content and face validity of the scale in the research. Exploratory (EFA) and Confirmatory Factor (CFA) analyses were performed to assess the construct validity of the scale.  Based on the results, it was found that the scale had a structure consisting of two dimensions and 18 items. It was determined that the factor loadings of the items in the scale were between .70 and .93. Considering the relevant literature, it was decided to name these dimensions as "natural observation skill" (NOS) and "scientific observation skill" (SOS). The Cronbach Alpha for the scales were both .95. As a result of the research, a valid and reliable scale that can determine the level of teachers' observation skills was developed.